2023
DOI: 10.3390/rs15102656
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Deformation of the 2023 Turkey Mw 7.8 and Mw 7.7 Earthquake Sequence Obtained by Fusing Optical and SAR Images

Abstract: In February 2023, Mw 7.8 and Mw 7.7 earthquakes struck southeastern Turkey. Generating a coseismic 3D deformation field that can directly reflect the characteristics of surface deformation is important for revealing the movement mode of a seismogenic fault and analyzing the focal mechanism. Optical image sub-pixel correlation (SPC) only captures deformation in the horizontal direction, and SAR image pixel offset tracking (POT) obtains range deformation that is not sensitive to north–south deformation signals. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 38 publications
0
1
0
Order By: Relevance
“…Notable instances include the 2023 Turkey earthquake sequence, marked by a Mw 7.8 earthquake near the Syrian border, followed by a Mw 7.5 quake 90 km to the north, both along the East Anatolian Fault Zone-a left-lateral strike-slip fault separating the Anatolian Plate from the Arabian Plate [33,34]. These studies, using diverse methods like image fusion and seismic source modeling [33][34][35], reveal the complex geodynamic setting in the broader region, characterized by a rich seismic history and numerous active faults with diverse directions and kinematics. Furthermore, the Mediterranean region boasts a centuries-long written record documenting pre-instrumental seismicity (prior to the 20th century).…”
Section: Study Area and Seismotectonic Settingmentioning
confidence: 99%
“…Notable instances include the 2023 Turkey earthquake sequence, marked by a Mw 7.8 earthquake near the Syrian border, followed by a Mw 7.5 quake 90 km to the north, both along the East Anatolian Fault Zone-a left-lateral strike-slip fault separating the Anatolian Plate from the Arabian Plate [33,34]. These studies, using diverse methods like image fusion and seismic source modeling [33][34][35], reveal the complex geodynamic setting in the broader region, characterized by a rich seismic history and numerous active faults with diverse directions and kinematics. Furthermore, the Mediterranean region boasts a centuries-long written record documenting pre-instrumental seismicity (prior to the 20th century).…”
Section: Study Area and Seismotectonic Settingmentioning
confidence: 99%
“…Three-dimensional coseismic surface deformation information about the Turkey double earthquakes has been obtained using the POT method and small-baseline subset persistent scatterer interferometry (SPC) methods [27]. Based on the deformation field and coseismic slip distribution of the two earthquakes, some prior researchers have conducted an in-depth analysis of the mutual triggering relationships among the Pazarcik, Elbistan, and Uzunba g earthquakes, and the impact of these earthquakes on the geological faults near the epicenter of the Pazarcik earthquake [2,28].…”
Section: Introductionmentioning
confidence: 99%
“…These data were then used to detect and analyze changes on the ground surface. An et al [15] combined horizontal deformation data from optical images with range and azimuthal offsets from SAR images to develop a comprehensive 3D deformation field for the 2023 Turkey earthquake sequence. The results indicated that the deformation of the Turkish earthquakes was predominantly oriented in an east-west direction.…”
Section: Introductionmentioning
confidence: 99%